Review of the taxonomic status of fossil Batomorphii from Southern Limon Basin, Costa Rica and description of a new species of Dasyatidae - Laurito, César A. (2021)
A taxonomic review of the rays [Batoidea] faunal assemblage from the Locality of Alto Guayacán, initially described by Laurito (1999), was made, same that was recovered from sediments of the Uscari Formation. The reason for making such revision is the remarkable advance in the knowledge of the dentition and the phylogenetic relationships of the recent and fossil rays. This is complemented by the multiple investigations on fossil Chondrichthyes from southern Central America and the Caribbean that have undoubtedly revolutionized the fossil record of the region. Many of the new species, then described for the Southern Limón Basin, have been validated and recognized by the scientific community and registered in other locations. However, it was necessary to review some of the previous determinations, in order to have an updated taxonomic record.